Uji effektifitas ekstrak etanol rosella (Hibiscus sabdariffa L) terhadap ketergantungan nikotin pada mencit putih jantan (Mus musculus) - Andriani, Yuni; Yulianingsih, Marza Nova; Suhatri, Suhatri (Tropharm (Trobosan Pharmacy); Vol 1 No 1 (2015): Tropharm (Trobosan Pharmacy), 2021)
Plants rosella (Hibiscus sabdariffa L ) is one of the drugs that have a high content of antioxidants, containing a variety of active substances and useful secondary metabolites that are often used as a free radical peroxidation substances. Researchers therefore lifting the title this study to see the effect of roselle plant extracts against nicotine broken state. The purpose of this study was to determine the effect of ethanol extract of roselle (Hibiscus sabdariffa L ) of the state of breaking nicotine in male white mice. Experimental animals were divided into 5 groups, namely the negative control experiments (mice with 0.2 ml saline and nicotine induction 5 mg / kg BW), the comparison group (mice by administering paracetamol 10 mg / kg and 5 mg nicotine / kg) , rosella extract group 2.6 mg / 20 g bb, rosella extract group 5.2 mg / 20 g bw, the roselle extract 10.4 mg / 20 g mm and nicotine 5 mg / kg. All groups after 30 min of extract of roselle induced by nicotine 5 mg / kg for 14 days. On the 15th day after the last nicotine in the morning, do the termination of nicotine by using diclofenac sodium 3.2 mg / kg. At the end of the experiment, carried out physical tests (grooming, preaning, chewing, licking and rearing), and psychological test (immobility time test and tail flick test). Results rosella extract dose 10.4 mg / 20 g bb show significant reductions in test physical reactions than other groups (p < 0.05). Rosella ethanol extract at a dose of 10.4 mg / 20 g bb also affects the psychological reaction test (p > 0.05).